Validation of non‐negative matrix factorization for rapid assessment of large sets of atomic pair distribution function data - Liu, Chia-Hao; Wright, Christopher J.; Gu, Ran; Bandi, Sasaank; Wustrow, Allison; Todd, Paul K.; O'Nolan, Daniel; Beauvais, Michelle L.; Neilson, James R.; Chupas, Peter J.; Chapman, Karena W.; Billinge, Simon J. L. (Journal of applied crystallography, 2021)
The use of the non‐negative matrix factorization (NMF) technique is validated for automatically extracting physically relevant components from atomic pair distribution function (PDF) data from time‐series data such as in situ experiments. The use of two matrix‐factorization techniques, principal component analysis and NMF, on PDF data is compared in the context of a chemical synthesis reaction taking place in a synchrotron beam, applying the approach to synthetic data where the correct composition is known and on measured PDFs from previously published experimental data. The NMF approach yields mathematical components that are very close to the PDFs of the chemical components of the system and a time evolution of the weights that closely follows the ground truth. Finally, it is discussed how this would appear in a streaming context if the analysis were being carried out at the beamline as the experiment progressed. The use of the non‐negative matrix‐factorization technique is validated for automatically extracting physically relevant signals from atomic pair distribution function data in the context of in situ measurement with a newly developed software infrastructure.